Determinants of financial well-being among young adults in Peninsular Malaysia - Anthony, Mervin (2022)
The desirability for young adults (18-29 years old) to achieve personal financial success is linked to determinants such as financial literacy, financial socialization, financial technology and self-control. Troubled by the high cost of living, the effects of covid-19 pandemic and the after effects of the pandemic young adults in Malaysia’s financial well-being has become more perilous. Therefore, the major objective of this study was to examine the determinants that affect financial well-being of young adults, the role of financial behaviour as a mediator and the moderating role of gender. A multi stage random sampling method was performed to draw a representative sample of Malaysian young adults, and 360 duly filled responses were received through selfadministered questionnaire through smart partnership with Malaysian Youth Council and the Malaysian Ministry of Youth and Sports. Descriptive analysis was conducted in order to summarize the empirical analysis results and factor analysis was done to measure the validity and reliability of the designed survey. This study used SEM-method. The SEM analysis covered the direct, indirect effect, and moderating effect assessment after the inspection of measurement model. In the context of this study, the System Theory, Unified Theory of Acceptance & Use of Technology (UTAUT), Theory of Self-Control and the Theory of Social Learning, are adapted and incorporated to propose the conceptual framework of young adult’s financial well-being. The results showed that there were positive significant relationships and direct effect between financial literacy (β= 0.12, Z = 2.40, p< 0.05), financial socialization (β= 0.40, Z = 4.97, p< 0.05), self-control (β= 0.19, Z = 2.41, p< 0.05), financial technology (β= 0.29, Z = 4.03, p< 0.05), with financial well-being of young adults. Financial behaviour (β= 0.48, Z = 3.10, p< 0.05) was the most significant determinant of financial wellbeing. Rapid developments of fintech in Malaysia are expected to contribute to improvement of young adult’s financial well -being. This research found fintech has significant and direct effect on financial behaviour and fintech was found to have significant effect on young adult’s financial wellbeing. In testing the mediation, the results showed the mediation effect of financial behaviour in the relationships between financial literacy and financial well-being, (β= 0.71, p< 0.05), between financial socialization and financial well-being, (β= 0.19, p< 0.05), between self-control and financial well-being, (β= 0.05, p< 0.05) and between financial technology and financial well-being (β= 0.01, p< 0.05). Another objective of this study was to analyse how gender of young adults moderates the relationship between financial behaviour and financial well-being. The results indicated that there is an insignificant moderating effect of male in the relationship between financial behaviour and financial well-being (β= 0.26, t= 1.388, p=0.16). The relationship between financial behaviour and financial well-being is stronger when its controlled for gender. In contrast, the results indicated that there is a significant moderating effect of female in the relationship between financial behaviour and financial well-being (β= 0.73, t= 2.649, p= 0.08). The study found, the regression slope for male respondents is 0.26 and not significant and the regression slope for female respondents is 0.73 and significant. In other words, the effect of financial behaviour on financial wellbeing depends on the gender of respondents whereby the effect is not significant for male respondents, while the effect is significant for female respondents. The findings are in good agreement with relevant theories proposed. Therefore, the current study has both the theoretical and practical contributions, and offers experts with actionable insights regarding the determinants of young adults’ financial well-being when designing policies to enable them from moving from a state of lower to higher financial well-being over time. This research has shown considerable evidence that young adults financial wellbeing can only happen through positive financial behaviour. As such, this research’s public policy recommendation are for young adult’s to be made aware of the pitfalls to avoid in using fintech applications, the good aspects of it as well as for female gender specific financial literacy programmes to help them in the attainment of their financial well-being. As financial behaviour developes over time, this study suggests a move away from one-off programmes to a move structured programme as a means of helping young adults develop positive financial behaviours.